Analysis of the Impact of Budget-Refocusing Policies on the Sustainability of Construction Services Companies - Aasniari, Aasniari; Anwar, Ruslin; Rachmansyah, Arief (International Journal of Science, Technology & Management, 2023)
Business actors in the construction sector in the pre-pandemic period showed good performance, the projects obtained were on target, contract values rose, and operating income increased, until stable liquidity there was no minus, so, before the pandemic, projects were planned according to their schedules, the right targets, to the appropriate cost plan, but after the pandemic, hence the emergence of the government's policy on diverting the project budget for disasters (Covid 19), where this policy is called budget refocusing, the regulation is contained in the 'Regulation of the Minister of Finance of the Republic of Indonesia Number 87 / PMK.07 / 2020'. During the pandemic, construction work can hinder the implementation of the proposed project to show declining performance. The purpose of this study is to find out the factors that influence consultants in construction management activities and also to find out the impact of government policies on budget refocusing on construction project planning. Data collection was carried out by survey through a questionnaire, the respondents to this study were those in a Surabaya consulting company that was directly involved in the field of building construction that was affected by budget refocusing. As for the results of factor analysis in the correlation analysis test, one factor that significantly influences consultants in construction management activities is the factor of high labor wages with a correlation of 0.709. And for the impact of budget refocusing on construction project planning on cost factors, where the indicator is the untimely payment with a test value of 4,369.